Keabsahan “Tungku” (Perkawinan Sedarah) di Kota Borong Kabupaten Manggarai Timur Nusa Tenggara Timur didalam Perspektif Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan dan Hukum Adat Manggarai - Maria Layticya Lasmi Latu; Orpa J Nubatonis; Rini Marselina Kaesmetan (Artemis Law Journal, 2026)
Basically, marriage has a long term goalas desired by humans themselves in order to foster a harmonious, paeceful and happy life in an atmosphere of love from two types of creatures created by Allah. This paper uses a qualitative research that produces descriptive data in the form of written or spokenn words of people and observable behavior. The results of this study shows that one of the clashes was found in the encounter between Cathoilc marriage law and the marriage model in the Manggarai culture. Church law is in the context of Manggarai culture which has customary law about customary marriage. In the catholic chruch marriage law, one of the obstacles is if the couple has a blood relationship. The concept of Catholic religious marraige is very contrary to understanding of Tungku marriage in Mangarai culture. The model according to the religious law and belief of each party that carries of Tungku marriage is a form of marriage tradition. It can be concluded that consanguineous marriage (Tungku) have violated the provisions of Article 8 of Law Number 1 of 1974 which regalutes the prohibition of consanguineous marriage becaus there is still a blood relationship between siblings. And consanguineous marriage (Tungku) that have been carried out in the traditions of the Manggarai coumminity are considered valid according to the customary law of the Manggarai community.